Moderation as a Solution to Religious Harmony in Poso Central Sulawesi - Firmansyah, Eka; Idris, Abdelmajid (NAJAHA, 2024)
This study aims to formulate religious moderation in overcoming identity conflicts and creating religious harmony in Poso, Central Sulawesi, which has long plagued inter-religious conflicts. Identity conflicts very often occur, both on a national and international scale. On a national scale, no one doubts that Poso Regency is a region capable of reviving and freeing itself from the identity conflicts they have experienced. At present, Poso Regency is very suitable to be used as a laboratory for studies on religious harmony. This research was conducted with a qualitative approach. The data collection was done by observing, interviewing, and reading from published literature. From this research, it was found that there are several ways to overcome identity conflicts and create religious harmony, 1) Respect the rituals of worship of other religions, 2) Implement noble morals between religious communities, 3) Build cooperation between religious communities, 4) Creating a broad-minded generation. The implications of what has been done are as follows, 1) A safe environment is formed, 2) it is free from identity conflicts, 3) religious harmony is created, and 4) regional development is more rapid.